The role of culture in the restoration and dissemination of the national spirit - Avramović, Zoran (Napredak, 2022)
The paper determines the basic and related concepts of culture. It points to the narrower and broader understanding of culture. The outstanding concepts are as follows: cultural patter, media culture, electronic culture, Serbian culture and foreign cultures, and Serbian cultural space. The second part is dedicated to major actors in culture, creators/authors, their works, the audience, institutions and organizations, cultural groups, state institutions with divided competences. The third part speaks of the restoration and dissemination of the national spirit (values) through two foundation pillars of culture – tradition (cultural heritage) and creative work. The fourth part casts light on the conflict nature of culture. The concluding part presents the attitude about the democratic struggle for cultural values.
Keywords: culture; national values; actors in culture; conflict in culture